2017
DOI: 10.1055/s-0043-112492
|View full text |Cite
|
Sign up to set email alerts
|

Exploring diagnostic and therapeutic implications of endoscopic mucosal resection in EUS-staged T2 esophageal adenocarcinoma

Abstract: IntroductionThe incidence of esophageal adenocarcinoma (EAC) has increased rapidly over the last three decades [1,2]. Although therapeutic protocols for early-and late-stage esophageal tumors have been well defined, treatment strategies for clinicalstage T2N0M0 tumors (cT2N0M0) are subject to debate owing to the relative inaccuracy of endoscopic ultrasound (EUS) staging, with profound implications in overstaged patients [3 -6]. A minimally invasive endoscopic resection is recommended for cT1 EACs. Only when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…In both studies, reassessment of selected EUS-staged cT2N0M0 patients treated by EMR resulted in downstaging of 40-50% of the tumours in which curative ER was also achieved with no major complications. 50,51 In future investigations, emphasis on high-risk histopathological and/or molecular markers for LNM that could be assessed in the ER specimen is needed to enable stage-guided treatment decisions, i.e. organ-sparing endoscopic treatment versus radical surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, reassessment of selected EUS-staged cT2N0M0 patients treated by EMR resulted in downstaging of 40-50% of the tumours in which curative ER was also achieved with no major complications. 50,51 In future investigations, emphasis on high-risk histopathological and/or molecular markers for LNM that could be assessed in the ER specimen is needed to enable stage-guided treatment decisions, i.e. organ-sparing endoscopic treatment versus radical surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the treatment options for cT2N0 disease, the main area of contention is on the role of neoadjuvant chemoradiotherapy prior to surgical resection. It should be briefly mentioned that endoscopic resection has been explored in one study in this patent group (15), reflecting the frequent overstaging of cT2N0 patients. This approach has not been adopted widely, and most cT2N0 patients will receive more radical treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…Data from the CROSS trial suggests that a substantial portion of these patients have more advanced disease at the time of resection, would have improved R0 resection rates with neo-adjuvant chemoradiotherapy, and have better long-term survival with neo-adjuvant chemoradiotherapy [1]. Gotink et al report that over a third of these patients would be candidates for endoscopic therapy instead of more radical surgical resection [2].…”
Section: Variations In Current Guidelinesmentioning
confidence: 99%
“…After radiologic imaging with computed tomography (CT) and positron emission tomography (PET) scanning, endoscopic ultrasound (EUS) has been the "standard ofcare" method of evaluation for patients with suspected T2 disease. The data from Gotink et al add to a long series of studies documenting the limited accuracy of EUS in diagnosing T2 esophageal adenocarcinoma [2]. These studies have shown over-staging rates to be as high as 50 % [5 -7].…”
Section: Limitations Of Pretreatment Staging With Endoscopic Ultrasoundmentioning
confidence: 99%